The role of artificial intelligence on the overall success of SMES in the E-commerce sector - Low, Wai Ying (2024)
The main objective in undertaking this research project is to educate SMEs in the business sector about the role of artificial intelligence in the overall success of their business. Therefore, we studied various factors such as AI Recommendation system, AI customer service solution, AI inventory management, and AI driven-data analytics will have an impact on the success of SMEs in e-commerce sector. Using a quantitative approach, 200 questionnaires were distributed to Malaysians from SMEs in the business sector through Random Sampling technology.